2005
DOI: 10.1210/jc.2004-1330
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Production of Gastric Ghrelin in Chronic Gastritis Associated withHelicobacter pylori

Abstract: Ghrelin is primarily secreted from the stomach and has been implicated in the coordination of eating behavior and weight regulation. The effects of Helicobacter pylori infection on plasma ghrelin concentration and gastric ghrelin production still have not been well known. We determined plasma ghrelin concentration in a total of 160 consecutive individuals with normal body mass index including 110 H. pylori-infected and 50 H. pylori-negative subjects. The expression levels of ghrelin mRNA and ghrelin-producing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
133
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(155 citation statements)
references
References 27 publications
12
133
5
Order By: Relevance
“…Plasma ghrelin concentrations in these patients are not decreased, in contrast to results reported in DM1 patients and in CAG due to H. pylori infection (4,5). The fact that plasma ghrelin concentrations were not low in our DM1-CAG patients could be explained by the results obtained on histologic studies.…”
Section: Discussioncontrasting
confidence: 80%
See 3 more Smart Citations
“…Plasma ghrelin concentrations in these patients are not decreased, in contrast to results reported in DM1 patients and in CAG due to H. pylori infection (4,5). The fact that plasma ghrelin concentrations were not low in our DM1-CAG patients could be explained by the results obtained on histologic studies.…”
Section: Discussioncontrasting
confidence: 80%
“…On the other hand, endocrine hyperplasia of ECL due to an increase in gastrin levels secondary to achlorhydria is a frequent finding in gastric mucosa of CAG patients (17). Although ghrelin is known to be synthesised by X/A-like cells, immunohistochemical studies of ECL hyperplastic lesions in the setting of type A CAG, as well as gastric carcinoids, have shown that these lesions are strongly positive for ghrelin and do express ghrelin mRNA, which demonstrates that this cell population also synthesise the protein (5). For this reason, it has been hypothesised that ECL acquire the capability to synthesise ghrelin during proliferative states or that ghrelin is the product of a peculiar neoplastic cell population, increased by gastrin stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are data in adults to suggest that H. pylori may modify plasma concentrations and/or gastric mucosal expression of ghrelin (25)(26)(27)(28)(29)(30)(31) as well as gastric mucosal leptin levels (32). However, to our knowledge, only one cross-sectional study has examined, by means of 13C-urea breath test, the influence of H. pylori infection on serum ghrelin and leptin concentrations in children (33), but there are no longitudinal data on the effect of H. pylori eradication on serum ghrelin and leptin in children.…”
Section: Introductionmentioning
confidence: 99%